Competition policy costs to firms - Agostinho, André Demmich Barbosa (2015)
The existence of competition policy forces companies to adjust their behaviour. This is also costly. Using a database from a company on contracts, I will try to estimate if a specific competition policy disposition, supply contracts cannot be longer than 60 months, has costs for the coffee suppliers operating in the Portuguese “on-trade” coffee market. The estimation method used in this paper will be OLS. The results suggest that limiting the duration of exclusivity contracts to 60 months can be harmful to the coffee suppliers and it can even seriously affect the market functioning. Key